A Survey of Ontologies Considering General Safety, Security, and Operation Aspects in OT - Siegfried Hollerer; Thilo Sauter; Wolfgang Kastner (IEEE Open Journal of the Industrial Electronics Society)
The integration of information technology (IT) and operational technology (OT) is deepening, amplifying the interconnectedness of operational, safety, and security demands within industrial automation systems. Lacking comprehensive guidance, risk managers often resort to manual solutions based on best practices or rely on domain experts, who usually offer insights limited to their specific areas of expertise. Given the intricate interplay among these domains, employing ontologies for knowledge representation could hold the key to capturing all necessary relationships and constraints for effective risk management processes. This study conducts a systematic mapping analysis of ontologies published over the past five years, focusing on at least one domain relevant to OT system risk management. Its objective is to categorize papers, offer a panoramic view of research themes and contributors, discern potential publication patterns, and identify research avenues based on a comprehensive review of these ontologies. Findings indicate a relatively stable research interest, with most publications presenting proof of concepts or initial experimental results for their ontological applications. This study establishes a foundation for classifying comprehensive OT ontologies and pinpoints unresolved issues that can steer future research efforts. It offers insights into the current state-of-the-art within this research area.